PENGGUNAAN METODE PESAWAT BERTANYA UNTUK MENINGKATKAN PRESTASI DAN MOTIVASI BELAJAR SISWA KELAS VII-F SMP NEGERI 1 WELERI KABUPATEN KENDAL - Hidayati, Juni (Fakultas Ekonomi, Universitas Negeri Semarang, 2012)
The purpose of this research is to improve students academic achievement and motivation using the plane asked. Action research was conducted at SMP Negeri 1 Weleri with research subjects class VII-F by 30 students. Implementation research is conducted in two cycles. Data collecting technique consists of two data, test data and non-test. The results showed learning by using the asking plane can improve student achievement. This is evidenced by the increase in value by 53% a write test, and the achievement of the KKM (Minimum Completences Criteria) on aspects of an increase of 40% is exceeded. Learning process by using the asking plane capable of increasing student motivation VII-F class. Indications of this increase can be seen from the data increases in value by 36,7% motivation. Development of studentâs behavior increase. The studentâs abily to respond and answer the questions rose by 3,33%. Student activity in listening increase of 3,33%. Student skills in presenting the material to rise by 3,34%. While the student activity in discussion groups experienced increase of 0,83%.